77.7k views
3 votes
How to work it out


How to work it out ‍-example-1

2 Answers

2 votes

Answer: b = -1

Method:

1) Expand out 2(6b + 5)

2 × 6b + 2 × 5 = 2 + 4b

12b + 10 = 4b + 2

2) Subtract 10 from both sides

12b + 10 - 10 = 4b + 2 - 10

12b = 4b - 8

3) Subtract 4b from both sides

12b - 4b = 4b - 4b - 8

8b = -8

4) Divide both sides by 8

(8b) ÷ 8 = -8 ÷ 8

b = -1

5) Substitute back in to check

2(6(-1) + 5) = 2 + 4(-1)

2(-6 + 5) = 2 + -4

2(-1) = -2

-2 = -2


User Tushar Maru
by
5.3k points
1 vote
Brackets first

2 * 6b is 12b
2 * 5 is 10
first part is 12b +10

The equation now is 12b + 10 is equal to 2 + 4b
take 2 from both sides
12b + 8 is equal to 4b
take 12b from both sides
8 is equal to -8b
divide by 8
1 is equal to -1b

User Jkerian
by
5.4k points